Salient Practices Of Halal Management In Southeast Asia: A Systematic Literature Review - Ahmad Rafiki; Irwan Mohd Subri; Mas Nooraini Mohiddin; Sutan Emir Hidayat; Mohd Mahyeddin Mohd Salleh (Emerald Publishing, 2025)
Indexed by Scopus